ChemInform Abstract: Li5Cr9Ti4O24: A New Anode Material for Lithium‐Ion Batteries. Issue 47 (November 2015) - Lin, Chunfu; Deng, Shengjue; Shen, Hong; Wang, Guizhen; Li, Yanfang; Yu, Lei; Lin, Shiwei; Li, Jianbao; Lu, Li
Abstract: The theoretical capacity of Li4 Ti5 O12 is increased by combining Ti 3+ /Ti 4+ and Cr 2+ /Cr 3+ redox couples.